Pengaruh Kualitas Informasi, Kualitas Sistem, dan Kualitas Layanan terhadap Kepuasan Pengguna Aplikasi JakteBoat di Jakarta - Muhammad Dzaky Arief; Diena Noviarini; Fildzah Shabrina (INDO PUBLISHING, 2026)
This study aims to examine and analyze the effects of information quality, system quality, and service quality on user satisfaction with the Jaket Boat application, a boat ticket booking application managed by the Transportation Agency of the Special Capital Region of Jakarta, particularly for transportation services to the Seribu Islands. The increasing demand for digital transportation services that are fast, accurate, and easily accessible highlights the need to evaluate the effectiveness of application-based public service systems in supporting maritime transportation. This study employed a quantitative research method with a descriptive approach. Data were collected through a questionnaire using a five-point Likert scale distributed to 180 active users of the Jaket Boat application selected through purposive sampling. The findings indicate that information quality, system quality, and service quality each have a positive and significant effect on user satisfaction. Among these variables, service quality has the strongest influence on user satisfaction. Conversely, technical issues and inaccurate information reduce user satisfaction. Therefore, this study recommends that the Jakarta Transportation Agency continuously improve application performance, customer service quality, and real-time information accuracy to enhance user convenience, trust, and satisfaction with digital maritime transportation services.